ANALISIS PENDAPATAN MASYARAKAT DARI BUDIDAYA MADU TRIGONA (TRIGONA SP.) DESA PEMEPEK KECAMATAN PRINGGARATA LOMBOK TENGAH - NINGRAT, JAYA; HARSONO, IWAN; YUDHA, I DEWA KETUT; FIRMANSYAH, FIRMANSYAH (Universitas Mahasaraswati K. Mataram, 2023)
This research aims to analyzed the level of the average income of the people of pemepek village of pringgarat sub-district central lombok regency from trigonasip honey bee cultivation, and to also analyze the contribution of the level of income from Trigona sp honey bee cultivation towards the respondent income. The type of data used in this research is qualitative and quantitative, the source of data used is from primary data and secondary data. The data collection method used in this research is observation, interview, and questionnaire with the aim to explore data verbally.The result of this research showed the average net profit from Trigona sp honey bee business in pemepek village of pringgarat sub-district central lombok regency is Rp 10.092.459/ year from 3 (three) productions in 1 (one) year. The struggle faced by Trigona sp honey bee farmer in pemepek village is that it is rather difficult to find new honey bee colony. The Trigona sp honey bee side business contribution towards the respondent household income in pemapek village is huge, where the Trigona sp honey bee side business achieve 66%, which is the highest presentation compared to other non-farming business income. Pemepek village's Trigona sp honey in the interest of business worthiness is very worthy to develop due to achieving R/C > from 1 that in the amount of 22,6 R/C thus it could be presumed to be worthy to be ran in pemepek village of pringgarat sub-district central lombok regency.